The comparision of various analytic techniques of the suspensions particles size distribution from enrichment process of copper ore - Kowalski, W.; Banaś, M.; Roman, M. (Видавництво Національного університету “Львівська політехніка”, 2005)
In the article there are described researches of particle size pattern in the float fluid of ore copper made by means of two different methods: analyses of the particle size in the stream of infrared rays stream, and analyses by use of sedimentation weight. Results of sedimentation process simulation are shown with use of certain parameters of particle composition. Used measurement techniques were analyzed whether they are useful for the industrial suspended particle fluids analyses.